2019
DOI: 10.1038/s41405-019-0014-z
|View full text |Cite
|
Sign up to set email alerts
|

Dentinogenesis imperfecta in Osteogenesis imperfecta type XI in South Africa: a genotype–phenotype correlation

Abstract: Background The maxillofacial and dental manifestations of Osteogenesis imperfecta (OI) have significant implications in terms of management. Although the occurrence of abnormal dentine in some forms of OI is well documented, there is scant information on the association of abnormal dentine in the Black African persons with phenotypic OI III and genotypic OI XI in South Africa. Methods This was a cross-sectional analytic study. A series of 64 Black South African individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In addition, in recent decades, genetic studies have been carried out that have allowed a better understanding of both the etiopathogenesis of OI and its relationship with the systemic and dental phenotypes [ 32 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Secondary to the early diagnosis of current OI, often even during pregnancy, the vast majority of these subjects have received pharmacological treatment from birth, usually with intravenous bisphosphonates, so it is not surprising that a relationship is found between the period or dose of administration of these drugs and the radiographic results of DGI-I [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in recent decades, genetic studies have been carried out that have allowed a better understanding of both the etiopathogenesis of OI and its relationship with the systemic and dental phenotypes [ 32 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Secondary to the early diagnosis of current OI, often even during pregnancy, the vast majority of these subjects have received pharmacological treatment from birth, usually with intravenous bisphosphonates, so it is not surprising that a relationship is found between the period or dose of administration of these drugs and the radiographic results of DGI-I [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in South Africa assessed osteogenesis imperfecta (OI) type 3, which has an unusually high frequency in the Black Southern African populations ( 105 ) Out of 91 patients with a confirmed phenotypic diagnosis of OI type 3, 45% of affected individuals had a pathogenic variant of the FKBP10 gene ( 105 ). Interestingly, the individuals with a homozygous mutation in the FKBP10 gene have clinically unaffected teeth yet exhibited radiographic features of dentinogenesis imperfecta to varying degrees ( 106 ). Another study evaluating the physical features of 125 individuals with Noonan syndrome found that Black Africans had the most distinctive features ( 107 ) however, the molecular detection rate in this study was only 31.2% compared to the expected >70% using whole exome sequencing (WES).…”
Section: Rare Diseasesmentioning
confidence: 99%
“…Again, open access publishing removes those barriers. There were four such papers published in 2019-2020, 40,41,42,43 including Chetty et al's 'Dentinogenesis imperfecta in osteogenesis imperfecta type XI in South Africa: a genotype-phenotype correlation' 41 and Khan et al's ' Analysis of different characteristics of smile' . 43…”
Section: Broader Applications Of Dentistrymentioning
confidence: 99%